Impact of alternative regional trade arrangements on the Ethiopian economy - Habtamu Shiferaw Amogne; Taiji Hagiwara (Journal of Economic Structures, 2021)
The Common Market for Eastern and Southern Africa (COMESA) is a Free Trade Area (FTA) regional trade agreement in Africa. Currently, Ethiopia is negotiating to join COMESA FTA. This study assesses the impact of three regional trade arrangements, COMESA FTA, customs unions, and the European Partnership Agreement (EPA) on the economy of Ethiopia. The analysis is based on a static Global Trade Analysis Project (GTAP) model, version 9 database. Unlike previous studies, the customs union scenarios are designed at the detailed Harmonized System (HS) level. COMESA FTA (scenario 1) with standard GTAP model results in a welfare loss for Ethiopia due to negative terms of trade and investment-saving effect, but with unemployment closure (scenario 2); Ethiopia enjoys a welfare gain mainly due to endowment effect. In scenario 3 (COMESA customs union) and scenario 4 (European Partnership Agreement), Ethiopia loses due to negative terms of trade and investment-saving effect. There is a large increase in demand for unskilled labor force in Ethiopia by around US23 million, US112 million, and US43 million for scenario 2, 3, and 4 respectively. Moreover, there is a positive output effect for oilseeds, leather, and basic metals across all scenarios. The world, as a whole, enjoys welfare gains with COMESA FTA (scenario 1 and 2). However, with scenario 3 and 4, there is an overall welfare loss. There is no strong reason for Ethiopia to move to the customs union, and the EPA in the short run. Therefore, a transition period is necessary, but it is recommended for Ethiopia to join COMESA FTA.
Keywords: F11; F13; F15; 330; COMESA; Customs union; EPA; Ethiopia; Free trade area; GTAP